Amphiphilic zein hydrolysate as a novel nano-delivery vehicle for curcumin. Issue 8 (5th August 2015) - Wang, Yong-Hui; Wang, Jin-Mei; Yang, Xiao-Quan; Guo, Jian; Lin, Yuan
<x xml:space="preserve">Abstract</x> We developed amphiphilic zein hydrolysate as a novel delivery vehicle, which could be used for preparation of curcumin-loaded nanoparticles (<50 nm). These nanoparticles have a great application potential in nutraceutical-fortified food and clear beverages.